Treatment of cross-cultural characteristics in the teaching of speaking to grade 12A1 students of English in Nam Dan 1 High school in Nghe An province - Hồ, Thị Mỹ Hạnh (ĐHNN, 2017)
When students learn a foreign language, their ultima te aim should be directed towards the understanding of the ways people do things and why they do them. At the same time language teachers also feel that while this goal is the most ideal, it is not very easy to handle, due partly to our imbalanced knowledge of more than one dicipline, partly also to time limitation in the classrooms. Students also have to face a unique problem of not being able to get themselves exposed to the natural environment while pursuing their language study. Therefore, they have to be equipped with cross-cultural knowledge to learn foreign language more effectively.